2006
DOI: 10.1021/bi061592m
|View full text |Cite
|
Sign up to set email alerts
|

(±)-(1S,2R,5S)-5-Amino-2-fluorocyclohex-3-enecarboxylic Acid. A Potent GABA Aminotransferase Inactivator that Irreversibly Inhibits via an Elimination−Aromatization Pathway

Abstract: Inhibition of γ-aminobutyric acid aminotransferase (GABA-AT) raises the concentration of GABA, an inhibitory neurotransmitter in human brain, which could have therapeutic applications for a variety of neurological diseases including epilepsy. Based on studies of several previously synthesized conformationally-restricted GABA-AT inhibitors, (±)-(1S,2R,5S)-5-amino-2-fluorocyclohex-3-ene carboxylic acid (12) was designed as a mechanismbased inactivator. This compound was shown to irreversibly inhibit GABA-AT; sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Mechanistic pathway b is a direct aromatization of 14a/14b to yield a tight binding adduct 20a/20b, which is similar to the inactivation mechanism of another fluorinated cyclohexene analogue. 34 Mechanistic pathway c involves nucleophilic addition of Lys292 to conjugated olefin 14a/14b, yielding adducts 21a/ 21b.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Mechanistic pathway b is a direct aromatization of 14a/14b to yield a tight binding adduct 20a/20b, which is similar to the inactivation mechanism of another fluorinated cyclohexene analogue. 34 Mechanistic pathway c involves nucleophilic addition of Lys292 to conjugated olefin 14a/14b, yielding adducts 21a/ 21b.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Whereas, the application of substrate analogues as irreversible inhibitors has been applied previously in the enzyme research field, this approach has found limited application as a tool in transporter research. For example, Wang and colleagues (17) synthesized a series of fluorinated GABA analogs which functioned as irreversible inhibitors of GABA aminotransferase. In the present study, we selected for chloro- and mesyl- groups since they are better leaving groups compared to fluoride.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, molecules unable to cross the BBB, must rely on various endogenous transporters. [13] Some GABA analogues that are unsaturated between the amino and carboxylic group, including cis-amino crotonic acid, trans-amino crotonic acid, and aminotetrolic acid, are characterized by an increased specificity to recognize GABAergic receptors; [14][15][16][17] similarly, cyclic systems, such as gabaculine, a naturally occurring neurotoxin, analog of m-aminobenzoic acid (MABA) and GABA-AT inhibitor, are able to cross the BBB (Figure 1) [18][19][20] and these structures are closely related with our proposed compounds in the Table 1.…”
Section: Introductionmentioning
confidence: 99%